2015
DOI: 10.1080/03079457.2015.1055235
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons are resistant to experimental infection with H7N9 avian influenza virus

Abstract: To determine the susceptibility of pigeons to the newly emerged avian influenza virus subtype H7N9, we experimentally infected three different types of pigeons (meat, town, and racing) with two different doses (2 × 10(4) or 2 × 10(5) EID50) of H7N9 avian influenza virus A/Chicken/China/2013 by either intranasal and intraocular inoculation (IN + IO) or intravenous injection (IV). In addition, the potential transmission of H7N9 to pigeons by direct close contact with experimentally infected pigeons and chickens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The emergence of an avian H7N9 virus in China in 2013 resulted in evaluations of that virus in pigeons after the virus was isolated from both wild and domestic pigeons [ 60 ]. Pigeons experimentally inoculated with the emergent H7N9 virus showed high survival and minimal shedding of the virus [ 60 ], a finding similar to those found in two other studies [ 61 , 62 ]. Another experimental study of the emergent H7N9 virus simulated a live bird market where pigeons were exposed to infected animals in cages stacked above them; none of the pigeons became infected [ 63 ].…”
Section: Pigeons Doves: Order Columbiformes Family Columbidaesupporting
confidence: 81%
“…The emergence of an avian H7N9 virus in China in 2013 resulted in evaluations of that virus in pigeons after the virus was isolated from both wild and domestic pigeons [ 60 ]. Pigeons experimentally inoculated with the emergent H7N9 virus showed high survival and minimal shedding of the virus [ 60 ], a finding similar to those found in two other studies [ 61 , 62 ]. Another experimental study of the emergent H7N9 virus simulated a live bird market where pigeons were exposed to infected animals in cages stacked above them; none of the pigeons became infected [ 63 ].…”
Section: Pigeons Doves: Order Columbiformes Family Columbidaesupporting
confidence: 81%
“…Other poultry species including ducks were successfully infected but the quantity of virus shed suggested no significant role in the spread of the disease to humans (Pantin-Jackwood et al, 2016). Field samples from pigeons were positively tested for A(H7N9), but experimental studies demonstrated the resistance of A(H7N9) and suggested that they had a minor role, if any, as a source of infection (Liu et al, 2015). Unfortunately, no published field or experimental data are available for the HPAI variant of A(H7N9) in China to date.…”
Section: Domestic and Wild Birdsmentioning
confidence: 99%
“…The pathogenicity of AIVs in pigeons and the vulnerability of pigeons for various subtypes of avian influenza have investigated in some studies (Yamamoto et al 2011;Liu et al, 2015). Furthermore, the ability of pigeons in being carrier and reservoir for these viruses has been studied (Liu et al, 2007).…”
Section: Histopathologymentioning
confidence: 99%